Malena: Representation of Sexual Harassment against Women in Film - Naila Inas Zhafirah; Irwan Sarbeni; Salsa Solli Nafsika (Universitas Pendidikan Indonesia, 2022)
The rise of sexual harassment against women has become a social issue that is constantly being discussed. This creates a statement that women are visual objects where women are always seen and cared for by the social environment both from their appearance and behavior. Sometimes, sexual harassment against women instead of making women victims, on the contrary, women are used as objects and are often blamed for the clothes they wear. It can be seen that the appearance of a woman can be a public assessment. This social issue is contained in the neat film Malena, a film that tells about a beautiful widow who is seduced by all the men in Sicily. In this film, the male point of view shows that harassing beautiful women is a pleasure and getting beautiful women is a trophy for them. In essence, the journal entitled